Scene construction impairments in Alzheimer's disease – A unique role for the posterior cingulate cortex. (December 2015) - Irish, Muireann; Halena, Stephanie; Kamminga, Jody; Tu, Sicong; Hornberger, Michael; Hodges, John R.
Abstract: Episodic memory dysfunction represents one of the most prominent and characteristic clinical features of patients with Alzheimer's disease (AD), attributable to the degeneration of medial temporal and posterior parietal regions of the brain. Recent studies have demonstrated marked impairments in the ability to envisage personally relevant events in the future in AD. It remains unclear, however, whether AD patients can imagine fictitious scenes free from temporal constraints, a process that is proposed to rely fundamentally upon the integrity of the hippocampus. The objective of the present study was to investigate the capacity for atemporal scene construction, and its associated neural substrates, in AD. Fourteen AD patients were tested on the scene construction task and their performance was contrasted with 14 age- and education-matched healthy older Control participants. Scene construction performance was strikingly compromised in the AD group, with significant impairments evident for provision of contextual details, spatial coherence, and the overall richness of the imagined experience. Voxel-based morphometry analyses based on structural MRI revealed significant associations between scene construction capacity and atrophy in posterior parietal and lateral temporal brain structures in AD. In contrast, scene construction performance in Controls was related to integrity of frontal, parietal, and medial temporal structures, including the parahippocampal gyrus and posterior hippocampus. The posterior cingulate cortex (PCC) emerged as the common region implicated for scene construction performance across participant groups. Our study highlights the importance of regions specialised for spatial and contextual processing for the construction of atemporal scenes. Damage to these regions in AD compromises the ability to construct novel scenes, leading to the recapitulation of content from previously experienced events.